Reassessment of the electrical connection between the pulmonary veins and the left atrium: A study to determine the different contributions of myocardial fibers along the standard ablation circumference - Bieito Campos-García; Concepción Alonso-Martín; José M. Guerra; Zoraida Moreno-Weidmann; Francisco Méndez-Zurita; Rodolfo Montiel-Quintero; Andrés Betancur-Gutiérrez; Xavier Viñolas-Prat; Enrique Rodríguez-Font (Frontiers in Cardiovascular Medicine, 2023)
BackgroundCircumferential ablation around the ipsilateral pulmonary veins (PVs) is the standard strategy for atrial fibrillation ablation. The present study seeks to assess which regions of the standard ablation circumference are the main contributors to the venoatrial electrical connection.MethodsA total of 41 patients were included under a specific atrial fibrillation ablation protocol in which the anterior and posterior segments of the standard circumference, between the equatorial line of the superior and the inferior ipsilateral PVs, were ablated first. If PV isolation was not achieved, ablation was extended superiorly or inferiorly, on the basis of the earliest atrial activation recorded during pacing from inside the PV. Complete PV isolation and the length of the areas not requiring ablation (ANRA) at the time of electrical isolation were evaluated.ResultsAblation of the anterior and posterior segments of the standard circumference led to the isolation of 77% left-PV pairs and 51% right-PV pairs (p = 0,015). A superior extension was required in 23% left-PV pairs and in 46% right-PV pairs, while an inferior extension was required only in 10% left-PV pairs and in 11% right-PV pairs. PV isolation was achieved before completing the standard ablation circumference in 97% left-PV pairs and in 94% right-PV pairs, with a median ANRA of 36.9 (IQR: 30.9–42.1) mm in the left PVs [16.0 (IQR: 12.0–19.0) mm superior and 18.8 (IQR: 16.1–24.9) mm inferior, p < 0.01] and 36.9 (IQR: 30.2–41.0) mm in the right PVs [15.1 (IQR: 10.7–19.1) mm superior and 20.6 (IQR: 16.9–23.3) mm inferior, p < 0.01].ConclusionsThe myocardial fibers along the anterior and posterior regions of the standard ablation circumference are the main contributors to the electrical connection between the pulmonary veins and the left atrium. Ablation of these regions results in PV isolation in the majority of patients.